Electron correlation in molecules -- ab initio beyond Gaussian quantum chemistry - Hoggan, Philip E.; Ozdogan, Telhat; ScienceDirect eBooks (Cambridge, MA : Academic Press is an imprint of Elsevier, 2016)
Annotation This title presents a series of articles concerning important topics in quantum chemistry, including surveys of current topics in this rapidly-developing field that has emerged at the cross section of the historically established areas of mathematics, physics, chemistry, and biology.
Includes index.
Online resource; title from PDF title page (ScienceDirect, viewed February 17, 2016).
Elsevier
Keywords: Quantum chemistry; Electrons; SCIENCE / Chemistry / Physical & Theoretical; Electrons; Quantum chemistry; Electronic books